Analisis Regresi Spasial pada Indeks Pembangunan Manusia di Provinsi Sumatera Utara Tahun 2020 - Wenny Srimeinda Tarigan (Seminar Nasional Official Statistics, 2021)
Human Development Index (HDI) in an area is influenced by the HDI in adjacent areas. Factors that affect HDI can be analyzed through classical linear regression, but if it have taken into account the location, the spatial regression approach is a more suitable analytical method to use. The purpose of this research is to perform a spatial regression analysis on the HDI modeling in North Sumatera Province in 2020. This research gives the result that the spatial regression model used is the SAR model. A positive value of ρ indicates that an increase of the HDI in the area surrounding a district/city will increase the HDI in that district/city. The direct effect obtained is -0.5069455 while the indirect effect is -0.313711. The percentage of poor people has a significant negative effect, which means that an increase of the percentage of poor people will cause a decrease of the HDI in North Sumatera province in 2020. Therefore, the government is advised to take appropriate policies from an economic perspective, especially in reducing poverty so that it can increase the HDI in North Sumatera Province.